Israel and French America. On two Tropisms of Réjean Ducharme’s Novels - Nardout-Lafarge, Élisabeth (Oltreoceano - Rivista sulle migrazioni, 2024)
Since his debut on the French-language literary scene at the age of twenty-five, Réjean Ducharme (1941-2017) has been recognized as one of the most influential writers and playwrights in Quebec literature. Despite the immediate success of his first novel, L’Avalée des avalés, published by Gallimard in 1966, in both France and Quebec, he spent his life in anonymity, refusing to appear in public. The complete edition of his nine novels, recently published in Gallimard’s “Quarto” collection (ed. Nardout-Lafarge, with the collaboration of Monique Bertrand and Monique Jean, 2022), has shed new light on the work of the author, who died on 21 August 2017. This article focuses on the recurrent inscriptions of Israel and French America in several of his novels, L’avalée des avalés (1966), Le nez qui voque (1967), Dévadé (1990) and Va savoir (1994), which were published over a period of thirty years. They are referred to as “tropisms” to underline precisely the recurrence of these places which are not described but evoked, towards which, literally, the texts “turn” and which appear as privileged “orientations”, as well as fascinations, invested by fantasy and bookish memory. The aim is to bring the novel’s treatment of these two tropisms into dialogue with the discourses and representations of Israel and French America that circulate and evolve at the same time in Quebec society. In this way, a condemnation of the idea of country and homeland and, despite the irony of the texts, a kind of nostalgia appear.